PERANCANGAN MESIN CNC PLOTTER DENGAN APLIKASI GRBL KONTROL TIGA SUMBU - Eko Afrily Trisnanto; Akhmad Musafa (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2022)
In this final project, a CNC plotter machine has been designed with three-axis control GRBL application. The expected benefit from the theoretical results of this research is that it can add insight into skills and knowledge in robotics, especially using the Arduino UNO microcontroller and as a reference for researchers in conducting further research. This system is designed to configure the CNC Plotter machine on hardware so that it can carry out the engraving and marking process with the desired image pattern. The control system of this tool consists of several components such as 1 unit 12VDC 10A power supply, 1 unit Arduino Uno microcontroller board, 1 unit CNC Shield board, 2 units motor drivers, 2 units stepper motors, 1 unit servo motor and a pen plotter. To run this CNC Plotter, there are several steps, uploading the GRBL into the Arduino Uno microcontroller, creating images / patterns using inkscape, converting the resulting images in G-code form and uploading the converted data to the GRBL controller application that is already installed on the laptop. Furthermore, the microcontroller will get the data transferred in the form of G-code from the laptop, the microcontroller will read the data to order the CNC Plotter to move according to the data obtained. To produce an optimal image pattern, this CNC Plotter uses three axes, the x-axis is driven by the stepper motor, the y-axis is driven by the stepper motor, and the z-axis is driven by the servo motor.